FAKTOR-FAKTOR YANG MEMENGARUHI KEBERHASILAN PEMBERIAN ASI EKSKLUSIF PADA IBU BEKERJA DI KLINIK ANNY RAHARDJO - Pawestri, Nui; Herselowati, Herselowati (NHM PRESS, 2024)
In the Maternal and Child Health Profile, the percentage of exclusive breastfeeding for babies 0-6 months in 2020 was 69.62%. The percentage of DKI Jakarta's exclusive provision of breast milk (ASI) is the lowest on the island of Java in 2021. Optimal breastfeeding can prevent more than 823,000 child deaths & 20,000 maternal deaths every year. A decrease in exclusive breastfeeding often occurs when the baby is three months old because the mother returns to work after maternity leave. This study aims to determine the relationship between husband's support, workplace facilities and work duration on the success of exclusive breastfeeding among working mothers at the main Anny Rahardjo clinic, East Jakarta. 2023. This research is an analytical survey with a cross-sectional approach. The population in this study were working breastfeeding mothers aged 7-12 years who were examined at the main Anny Rahardjo clinic in the period July-December 2023. The sample size in this study was determined as mentioned using a total sampling of 132 respondents. The data analysis used was using the Chi square statistical test. There is a significant relationship between husband's support, facilities at work and duration of work on the success of exclusive breastfeeding for working mothers at the main Anny Rahardjo clinic, East Jakarta in 2023 with the results of husband's support, p value = (0.003), facilities at work p value = (0.002), and duration of work p value = (0.005). There is a relationship between husband's support, workplace facilities and work duration on the success of exclusive breastfeeding for working mothers at the main Anny Rahardjo clinic, East Jakarta.